From Theory to Practice: The Role of Psycholinguistics in Teaching English (Journal of Pedagogical Inventions and Practices, 2023)
This article explores the integration of psycholinguistic principles in the teaching of English in Uzbekistan, a context characterized by its unique linguistic and cultural landscape. It begins by defining psycholinguistics and its relevance to language teaching, followed by an examination of the historical development of the field and its key concepts. The discussion then shifts to the specific context of Uzbekistan, highlighting the linguistic diversity, cultural considerations, and cognitive challenges faced by Uzbek students learning English. The article reviews successful global examples of English teaching programs that have incorporated psycholinguistic approaches, analyzing their materials and methods. It further discusses the challenges and opportunities in applying these approaches in Uzbekistan, including the role of technology and digital media. Finally, the article concludes with recommendations for educators, policymakers, and suggestions for future research, emphasizing the potential of psycholinguistics to enhance English language education in Uzbekistan